The rationale for the treatment of long-Covid symptoms – A cardiologist's view - Schieffer, Elisabeth; Schieffer, Bernhard (Frontiers in Cardiovascular Medicine, 2022)
The ongoing coronavirus disease 2019 pandemic left us with thousands of patients suffering from neurological, cardiovascular and psychiatric disorders named post-acute sequelae of COVID-19 or just long-Covid. In parallel, the vaccination campaigns against SARS-CoV-2 spike protein saved millions of lives worldwide but long-Covid symptoms also appeared rarely following vaccination with a strong overlap to the “canonical” long-Covid symptoms. A therapeutical strategy targeting both, post-VAC and post-SARS-CoV-2 long-Covid symptoms is warranted since exposure to the S-protein either by vaccinating or SARS-CoV-2 infection may trigger identical immuno-inflammatory cascades resulting in long-Covid symptoms.